Darboux problem for the generalized Euler – Poisson – Darboux equation - Ismoilov, A. I.; Mamanazarov, A. O.; Urinov, A. K. (Ukrains’kyi Matematychnyi Zhurnal, 2017)
In the article Euler – Poisson – Darboux equation was considered in the characteristic triangle and Darboux problem was investigated. The solution of the problem was found by Riemann’s method. Theorems on the existence and uniqueness of the solution were proved.